Effects of cluster formation on spectra of benzo[a]pyrene and benzo[e]pyrene - Fioressi, Silvina E. (2008)
Absorption and fluorescence emission spectra of the polycyclic aromatic hydrocarbons benzo[a]pyrene (BaP) and benzo[e]pyrene (BeP) in solution and adsorbed on silica have been obtained and compared to examine the spectroscopic effects of clustering. Molecular mechanics calculations with the UFF potential were done to optimize monomer, dimer and trimer geometries, and energy differences were determined by MP2/6-31G* calculations. Fluorescence emission spectra of adsorbed BeP and BaP display a red shift that progresses with increased loading, and the two differ in their photodegradation kinetics. The experimental and theoretical results are found to be consistent.